Initiating a Marketing Mix in The Regulation of The Sale of State-owned Assets - Trisulo, Tri; Budi Susilo (Universitas Negeri Semarang, 2025)
State properties (BMN) that are auctioned do not always sell well at the first opportunity. Failure in the first auction could have an impact on the increasingly uneconomic value of the BMN because the condition can get worse/obsolete. This condition triggers the idea of implementing a marketing mix in regulations so that BMN sales are more optimal. This is legal research, intending to analyze the implementation of the principle